Environmental, biological and social factors contributing to new rises in COVID-19 morbidity in Russia - T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Биопрепараты: Профилактика, диагностика, лечение)
Morbidity surveys in certain regions during the COVID-19 pandemic have established that the infection spreads in a wave-like manner characterised with peaks and troughs in incidence. According to the analysis of COVID-19 epidemic development in Russia, surges in COVID-19 infections are mainly driven by seasonal factors, insufficient herd immunity, and emerging SARS-CoV-2 variants with increased transmissibility. The aim of the study was to analyse environmental, biological and social factors contributing to new rises in COVID-19 cases in Russia. The study covers the global epidemiological situation as of mid-2022 and the role of environmental, biological, and social factors in the spread of COVID-19 in the Russian Federation. The results suggest that new highly contagious SARS-CoV-2 variants and seasonality are the principal factors driving new rises in morbidity. The authors assume that the sixth and the seventh COVID-19 waves in Russia will be in line with the best case scenario, which predicts the spread of a SARS-CoV-2 variant with increased transmissibility and reduced virulence.